Pengenalan Bahasa Inggris Dasar Kepada Anak-Anak TK Besar dengan Menggunakan Lagu Anak Bilingual - Ni Wayan Artiniasih; Luh Made Dwi Wedayanthi (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service program aims to introduce basic English vocabulary to Kindergarten students through the medium of bilingual songs. The background of this activity is the limitation of interactive learning media and the dominance of traditional methods that are less attractive for early childhood. Bilingual songs were chosen because they have a simple rhythm, easy to remember lyrics, and are able to create a fun and contextual learning atmosphere. The method used is the Participatory Action Learning System approach which includes the preparation stage, flexible action, and reflection. Bilingual songs are inserted at the transition moments of class activities and combined with simple movements to stimulate natural vocabulary acquisition. The results of the observations showed a significant improvement in children's language skills: most students were able to remember new vocabulary, enthusiasm for learning increased, and active participation in singing together was higher. Teachers also reported that the use of bilingual songs helped keep children's attention and created a positive learning atmosphere. Overall, this activity proves that bilingual songs are an effective, fun, and appropriate medium for children's developmental stages to strengthen mastery of basic English vocabulary. This program is recommended to be applied continuously in daily learning activities in kindergarten classrooms.